The comparison between weekly and three-weekly cisplatin delivered concurrently with radiotherapy for patients with postoperative high-risk squamous cell carcinoma of the oral cavity - Tsan, Din-Li (BioMed Central, 2012)
BACKGROUND: The aim of this study was to compare the outcomes of postoperative adjuvant concomitant chemoradiotherapy using two different schedules of cisplatin for patients with high-risk oral squamous cell carcinoma (OSCC). METHODS: From Feb. 2008 to Aug. 2010, 55 patients with high-risk OSCC were included in this study. Patients were randomized into treatment groups that either received 100 mg/m(2) cisplatin once every 3 weeks (arm A) or 40 mg/m(2) cisplatin once per week (arm B). All patients were irradiated with 66 Gy in 33 fractions. RESULTS: Of the 50 eligible patients, 26 were assigned to arm A, and 24 were assigned to arm B. Both groups of patients received the same mean doses of radiotherapy and cisplatin. However, 88.5% of patients in arm A and 62.5% of those in arm B (p = 0.047) received ≥ 200 mg/m(2) of cisplatin in total. The overall toxicity was significantly greater in arm B (p = 0.020), and all of the grade 4 toxicities occurred in patients in arm B. CONCLUSIONS: Three-weekly high-dose cisplatin treatment showed higher compliance, and lower acute toxicity compared to weekly low-dose cisplatin treatment.